A Broader Perspective of Job Satisfaction in Higher Education Institutes of Indonesia - Siriattakul, Parinya; Jermsittiparsert, Kittisak; Abdurrahman, Abdurrahman (International Journal of Psychosocial Rehabilitation, 2019)
The study is carried out on the issues related to job satisfaction in the higher education institute of Indonesia. The study has studied the direct impact of the teamwork, organizational climate, and job insecurity on job satisfaction. Meanwhile, the study has also examined the moderating role of self-efficacy, and achievement orientation in the associations between teamwork, organizational climate, and job insecurity on job satisfaction. Or the purpose of data analysis, the Structural Equation Modeling is used in this study. The Structural equation modeling is a statistical multivariate technique for analyzing the structural associations. It is a combination of multiple regression analysis and factor analysis and is generally employed to analyze the existence of a structural association between the measured and the latent constructs. The findings of the study have shown agreement with the proposed findings and have argued the teamwork, organizational climate, and job insecurity as the determinants of job satisfaction of employees working in the higher education institutes of Indonesia. The study is among the pioneering study on the issue and will help the researchers and academicians in understanding the issue related to job satisfaction among the employees in the higher education institutions of Indonesia.